Anion exchange membrane, preparation method and application thereof and electrolysis device

By crosslinking the polymer main chain using crosslinking groups containing ether groups in the anion exchange membrane, the problems of poor ion conductivity and insufficient chemical stability of the existing anion exchange membrane are solved, and high conductivity and stability are achieved The electrolytic performance of the anion exchange membrane is improved.

CN119465289AActive Publication Date: 2025-02-18HYDROGEN & YUANTAI (CHANGZHOU) NEW MATERIALS TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411580127.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing anion exchange membranes have problems such as poor ion conductivity, insufficient chemical stability, and poor compatibility between the membrane and electrode interfaces, and the ionic conductivity and alkali resistance of the polyaryl piperidine anion exchange membrane still need to be improved.

Method used

The polymer backbone is crosslinked by crosslinking groups containing ether groups. The ether groups in the crosslinking group can effectively induce ionic groups to self-aggregate, thereby forming a developed ion transport channel, improving conductivity, and through introduction Crosslinking groups improve anti-swelling properties and enhance the dimensional stability of the film.

Benefits of technology

The conductivity and stability of the anion exchange membrane are significantly improved, the mechanical properties and micro-phase separation structure of the membrane are improved, and the electrolytic performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465289A_ABST
    Figure CN119465289A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolysis, and provides an anion exchange membrane, a preparation method and application thereof and an electrolysis device, the anion exchange membrane comprises a plurality of polymer main chains and a plurality of crosslinking groups, the plurality of polymer main chains are crosslinked through the plurality of crosslinking groups, and the crosslinking groups contain ether groups. The anion exchange membrane is high in conductivity and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrolysis technology, and in particular to an anion exchange membrane and a preparation method, application and electrolysis device thereof. Background Art

[0002] Hydrogen production by water electrolysis has become an important method of hydrogen production due to its simple principle and high energy efficiency. Among them, the key to water electrolysis lies in the electrolyte materials used in the electrolyzer, especially the performance of the membrane material, which directly affects the electrolysis efficiency and hydrogen production. Anion exchange membrane (AEM) type electrolyzer is a new type of electrolyzer technology that has developed rapidly in recent years. It has the advantages of low cost of traditional alkaline electrolyzers and high electrolysis efficiency of proton exchange membrane type electrolyzers. Quaternary ammonium salt anion exchange membrane and polyaryl piperidine anion exchange membrane are used in traditional technologies. Quaternary ammonium salt anion exchange membrane has problems such as poor ion conductivity, insufficient chemical stability and poor compatibility between membrane and electrode interface; the ion conductivity and alkali resistance of polyaryl piperidine anion exchange membrane still need to be improved. Therefore, how to improve the conductivity and stability of anion exchange membrane has become a technical problem that urgently needs to be solved. Summary of the invention

[0003] Based on this, an embodiment of the present application provides an anion exchange membrane with high conductivity and good stability, and a preparation method, application and electrolysis device thereof.

[0004] In a first aspect, the present application provides an anion exchange membrane, which includes a plurality of polymer main chains and a plurality of cross-linking groups, wherein the plurality of polymer main chains are cross-linked by a plurality of the cross-linking groups, and the cross-linking groups contain ether groups.

[0005] In some embodiments, the cross-linking group includes a cross-linking main chain and a cross-linking side chain grafted onto the cross-linking main chain, and the cross-linking main chain and / or the cross-linking side chain contain an ether group.

[0006] In some embodiments, the polymer backbone includes at least one of a polyarylpiperidine polymer, a polyarylisatin polymer, and a polybenzimidazole polymer.

[0007] In some embodiments, the mass ratio of the polymer main chain to the cross-linking group is 1:(0.06-0.5).

[0008] In a second aspect, the present application provides a method for preparing an anion exchange membrane, the preparation method comprising:

[0009] A solution containing a polymer main chain and a cross-linking agent are mixed to form a casting solution after cross-linking, and a prefabricated membrane is obtained after coating the casting solution, wherein the cross-linking agent contains an ether group;

[0010] The prefabricated membrane is subjected to ion exchange treatment to prepare the anion exchange membrane.

[0011] In some embodiments, the mass ratio of the cross-linking agent to the polymer main chain is (0.06-0.5):1.

[0012] In some embodiments, the mass concentration of the polymer main chain in the solution containing the polymer main chain is 5% to 25%.

[0013] In some embodiments, the crosslinking agent includes a polyhalogenated ether compound; optionally, the crosslinking agent includes at least one of 1,2-bis(2-chloroethoxy)ethane, 1,2-bis(2-bromoethoxy)ethane, 1,2-bis(2-iodoethoxy)ethane, 1,2-dichloro-1-ethoxyethane, 1,2-bis(4-chlorophenoxy)ethane, 1,2-bis(chloroacetoxy)ethane and 1,6-dibromo-2,5-dioxoperfluorohexane.

[0014] In some embodiments, the ion exchange treatment comprises:

[0015] Performing a first ion exchange treatment on the prefabricated membrane using a metal salt solution;

[0016] The prefabricated membrane is subjected to a second ion exchange treatment using an alkaline solution.

[0017] Optionally, the metal salt contained in the metal salt solution includes at least one of NaBr, NaCl and KBr.

[0018] Optionally, the alkaline compound contained in the alkaline solution includes at least one of potassium hydroxide, sodium hydroxide and calcium hydroxide.

[0019] In some embodiments, the method for preparing the polymer backbone comprises:

[0020] mixing an aromatic monomer and a ketone monomer to obtain a first solution;

[0021] Mixing the first solution and an acidic catalyst to prepare a polymer main chain intermediate;

[0022] The polymer main chain intermediate, the acid binding agent and the halogenated alkane are mixed to obtain a second solution, and the polymer main chain is obtained after quaternization.

[0023] In some embodiments, the molar ratio of the aromatic monomer to the ketone monomer is 1-1.2:1.

[0024] In some embodiments, the mass ratio of the halogenated alkane to the polymer main chain intermediate is (0.2~0.8):1.

[0025] In some embodiments, the mass ratio of the acid binding agent to the polymer main chain intermediate is (0.3~0.8):1.

[0026] In some embodiments, the aromatic monomer includes at least one of p-terphenyl, m-terphenyl, biphenyl, bibenzyl, and 9,9′-diphenylfluorene.

[0027] In some embodiments, the ketone monomer includes at least one of N-methyl-4-piperidone, isatin, 3-quininone, 1,1,1-trifluoroacetone, and 2,2,2-trifluoroacetophenone.

[0028] In some embodiments, the halogenated alkane includes at least one of methyl iodide, ethyl iodide, and 2-iodopropane.

[0029] In some embodiments, the acid binding agent includes at least one of potassium carbonate, sodium hydride, sodium bicarbonate, trimethylamine and sodium carbonate.

[0030] In some embodiments, the acidic catalyst includes at least one of trifluoroacetic acid, trifluoromethanesulfonic acid, methanesulfonic acid, perfluoropropionic acid, pentafluoroethanesulfonic acid, and heptafluorobutyric acid.

[0031] Optionally, the acidic catalyst comprises trifluoroacetic acid and trifluoromethanesulfonic acid. Further optionally, the molar ratio of the trifluoroacetic acid to the ketone monomer is 1-1.5:1; the molar ratio of the trifluoromethanesulfonic acid to the ketone monomer is 9-12:1.

[0032] In a third aspect, the present application provides a use of the anion exchange membrane as described in the first aspect in preparing an electrolysis device.

[0033] In a fourth aspect, the present application provides an electrolysis device, comprising the anion exchange membrane as described in the first aspect and / or an anion exchange membrane prepared by the method for preparing an anion exchange membrane as described in the second aspect.

[0034] Compared with the traditional technology, this application has at least the following beneficial effects:

[0035] The present application adopts cross-linking groups containing ether groups to cross-link the polymer main chain. The ether groups in the cross-linking groups can effectively induce the self-aggregation of ionic groups, thereby forming a developed ion transmission channel and effectively improving the conductivity. Moreover, the introduction of cross-linking groups into the anion exchange membrane can effectively improve its anti-swelling performance, thereby improving the dimensional stability of the anion exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1FT-IR spectra of the polymer backbones prepared in Example 3 and Comparative Example 1 of the present application;

[0037] Figure 2 This is a diagram of the mechanical strength of the anion exchange membranes prepared in Example 3 and Comparative Example 1 of the present application;

[0038] Figure 3 Polarization curves of alkaline water electrolysis performed by the electrolysis devices in Example 3 and Comparative Example 1 of the present application;

[0039] Figure 4 This is a comparison diagram of the microscopic morphology of Example 3 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0040] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0042] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0043] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0044] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0045] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0046] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0047] In the traditional technology, a hydrophobic cross-linking agent is introduced into the polymer main chain to prepare a cross-linked anion exchange membrane. Although the hydrophobic cross-linking structure can effectively inhibit the water absorption and swelling of the anion exchange membrane, enhance the dimensional stability of the membrane and improve the mechanical properties of the membrane, the introduction of the hydrophobic cross-linking structure will also sacrifice the ion exchange capacity of the anion exchange membrane, resulting in problems such as unclear microphase separation and low ion conductivity.

[0048] In a first aspect, the present application provides an anion exchange membrane, which includes a plurality of polymer main chains and a plurality of cross-linking groups. The plurality of polymer main chains are cross-linked by the plurality of cross-linking groups, and the cross-linking groups contain ether groups.

[0049] The present invention adopts cross-linking groups containing ether groups to cross-link the polymer main chain. The ether groups in the cross-linking groups can effectively induce the self-aggregation of ionic groups, thereby forming a developed ion transmission channel and effectively improving the conductivity. Moreover, the introduction of cross-linking groups into the anion exchange membrane can improve the anti-swelling performance, thereby improving the dimensional stability of the anion exchange membrane.

[0050] In some embodiments, the cross-linking group includes a cross-linking backbone chain, and the cross-linking backbone chain contains an ether group.

[0051] In some embodiments, the cross-linking group includes a cross-linking main chain and a cross-linking branch chain grafted onto the cross-linking main chain. For example, the cross-linking branch chain can be an alkyl group. Alternatively, the cross-linking main chain can contain an ether group; or the cross-linking branch chain can also contain an ether group; or, both the cross-linking main chain and the cross-linking branch chain contain an ether group.

[0052] It can be understood that the cross-linked main chain can be composed of an alkyl group, and the cross-linked side chain can also be composed of an alkyl group.

[0053] In some embodiments, the polymer backbone comprises at least one of a polyaryl piperidine polymer, a polyaryl isatin polymer and a polybenzimidazole polymer. Optionally, the polymer backbone comprises a quaternized polyaryl piperidine polymer. The present application adopts a quaternized polyaryl piperidine polymer as the polymer backbone, which cooperates with a cross-linking group containing an ether group, has good microphase separation and good swelling resistance, and can improve the ion conductivity and dimensional stability of the anion exchange membrane.

[0054] It is understood that in the present application, the polymer main chain can also be modified by grafting other modifying groups to improve the performance of the anion exchange membrane, for example, partially iodomethane the polymer main chain.

[0055] In some embodiments, the mass ratio of the polymer backbone to the cross-linking group is 1:(0.06-0.5), for example, 1:0.06, 1:0.10, 1:0.15, 1:0.20, 1:0.25, 1:0.30, 1:0.35, 1:0.40, 1:0.45 or 1:0.50. The present application selects the mass ratio of the polymer backbone and the cross-linking group as above to avoid problems such as the inability of the casting liquid gel to be cast into a film and the inability to successfully cross-link, thereby effectively ensuring the stability and conductivity of the anion exchange membrane.

[0056] The second aspect of the present application provides a method for preparing an anion exchange membrane, the preparation method comprising:

[0057] A solution containing a polymer main chain and a cross-linking agent are mixed to form a casting solution after cross-linking, and a prefabricated membrane is obtained after coating the casting solution, wherein the cross-linking agent contains an ether group;

[0058] The prefabricated membrane is subjected to ion exchange treatment to prepare the anion exchange membrane.

[0059] The present application prepares an anion exchange membrane as described above, and uses a cross-linking agent containing an ether group to cross-link the polymer main chain. The ether group in the cross-linking agent can effectively induce the self-aggregation of ionic groups, thereby forming a developed ion transmission channel and effectively improving the conductivity. Moreover, the introduction of cross-linking groups into the anion exchange membrane can improve the anti-swelling performance, thereby improving the dimensional stability of the anion exchange membrane.

[0060] In some embodiments, the mass ratio of the crosslinking agent to the polymer main chain is (0.06-0.5):1.

[0061] In some embodiments, the mass concentration of the polymer backbone in the solution containing the polymer backbone is 5% to 25%, for example, 5%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24% or 25%.

[0062] In some embodiments, the crosslinking agent includes a polyhalogenated ether compound, for example, a dihalogenated alkane containing an ether group may be used as the crosslinking agent.

[0063] Optionally, the crosslinking agent includes at least one of 1,2-bis(2-chloroethoxy)ethane, 1,2-bis(2-bromoethoxy)ethane, 1,2-bis(2-iodoethoxy)ethane, 1,2-dichloro-1-ethoxyethane, 1,2-bis(4-chlorophenoxy)ethane, 1,2-bis(chloroacetoxy)ethane and 1,6-dibromo-2,5-dioxoperfluorohexane.

[0064] In some embodiments, the solvent in the casting solution includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0065] In some embodiments, the casting solution is dried after being coated to obtain the prefabricated membrane. Optionally, the drying temperature is 60° C. to 100° C. and the drying time is 24 h to 36 h.

[0066] In some embodiments, the ion exchange treatment comprises:

[0067] Performing a first ion exchange treatment on the prefabricated membrane using a metal salt solution;

[0068] The prefabricated membrane is subjected to a second ion exchange treatment using an alkaline solution.

[0069] The present application performs ion exchange treatment as described above. Compared with ion exchange treatment using only alkaline solution, the ion exchange is fast and thorough.

[0070] Optionally, the metal salt contained in the metal salt solution includes at least one of NaBr, NaCl and KBr. Optionally, the molar concentration of the metal salt is 0.2 mol / L to 1 mol / L.

[0071] Optionally, the alkaline compound contained in the alkaline solution includes at least one of potassium hydroxide, sodium hydroxide and calcium hydroxide. Optionally, the molar concentration of the alkaline compound is 0.5 mol / L to 2 mol / L.

[0072] In some embodiments, the method for preparing the polymer backbone comprises:

[0073] mixing an aromatic monomer and a ketone monomer to obtain a first solution;

[0074] Mixing the first solution and an acidic catalyst to prepare a polymer main chain intermediate;

[0075] The polymer main chain intermediate, the acid binding agent and the halogenated alkane are mixed to obtain a second solution, and the polymer main chain is obtained after quaternization.

[0076] In some embodiments, after the first solution and the acidic catalyst are mixed, a first precipitant is added to precipitate to obtain a polymer backbone intermediate. Optionally, the polymer backbone intermediate is also washed and vacuum dried.

[0077] Optionally, the first precipitant includes at least one of anhydrous methanol, anhydrous ethanol, potassium hydroxide solution, sodium hydroxide solution, potassium carbonate solution, sodium carbonate solution and sodium bicarbonate solution.

[0078] Optionally, the vacuum drying temperature is 30°C to 100°C, and the time is 24h to 36h.

[0079] In some embodiments, the molar ratio of the aromatic monomer to the ketone monomer is 1-1.2:1, for example, 1.05:1, 1.10:1, 1.15:1 or 1.20:1.

[0080] In some embodiments, the mass ratio of the halogenated alkane to the polymer backbone intermediate is (0.2-0.8):1, for example, it can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1 or 0.8:1.

[0081] In some embodiments, the mass ratio of the acid binding agent to the polymer main chain intermediate is (0.3-0.8):1, for example, it can be 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1 or 0.8:1.

[0082] In some embodiments, the quaternization temperature is 30° C. to 40° C., the environment is protected from light, and the time is 24 h to 48 h.

[0083] In some embodiments, a second precipitant is added to the quaternized solution, and the precipitate is washed and dried after precipitation to obtain a polymer backbone. Optionally, the second precipitant includes at least one of ethyl acetate, acetone and diethyl ether.

[0084] In some embodiments, the aromatic monomer includes at least one of p-terphenyl, m-terphenyl, biphenyl, bibenzyl, and 9,9′-diphenylfluorene.

[0085] In some embodiments, the ketone monomer includes at least one of N-methyl-4-piperidone, isatin, 3-quinindone, 1,1,1-trifluoroacetone, and 2,2,2-trifluoroacetophenone.

[0086] In some embodiments, the halogenated alkane includes at least one of methyl iodide, ethyl iodide, and 2-iodopropane.

[0087] In some embodiments, the acid binding agent includes at least one of potassium carbonate, sodium hydride, sodium bicarbonate, trimethylamine and sodium carbonate.

[0088] In some embodiments, the acidic catalyst includes at least one of trifluoroacetic acid, trifluoromethanesulfonic acid, methanesulfonic acid, perfluoropropionic acid, pentafluoroethanesulfonic acid, and heptafluorobutyric acid.

[0089] Optionally, the acidic catalyst includes trifluoroacetic acid and trifluoromethanesulfonic acid.

[0090] Further optionally, the molar ratio of the trifluoroacetic acid to the ketone monomer is 1-1.5:1; the molar ratio of the trifluoromethanesulfonic acid to the ketone monomer is 9-12:1.

[0091] In some embodiments, the solvent contained in the first solution includes at least one of dichloromethane, trifluoroacetic acid, and trifluoromethanesulfonic acid.

[0092] In some embodiments, the solvent contained in the second solution includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0093] Exemplarily, a method for preparing the above anion exchange membrane is provided, comprising the following steps:

[0094] (1) Polymer main chain

[0095] The aromatic monomer and the ketone monomer are mixed in a molar ratio of 1 to 1.2:1 to obtain a first solution; an acidic catalyst is added to the first solution, reacted for 6 to 8 hours, and then a precipitant is added, the precipitate is washed to neutrality, and vacuum dried at 30° C. to 100° C. for 24 hours to 36 hours to obtain a polymer main chain intermediate;

[0096] The polymer main chain intermediate is dissolved, and then an acid binding agent and a halogenated alkane are added, and a quaternization reaction is carried out at 30° C. to 40° C. in the dark for 24 h to 48 h, and then a second precipitant is added, and the precipitate is washed with deionized water for multiple times, and then vacuum dried at 60° C. to 100° C. for 24 h to 36 h to obtain a polymer main chain;

[0097] (2) Prefabricated membrane

[0098] The polymer main chain is dissolved to form a solution with a mass concentration of 5% to 25%, a cross-linking agent is added to the solution containing the polymer main chain to obtain a casting solution, the mass ratio of the cross-linking agent to the polymer main chain is (0.06 to 0.5):1, the casting solution is coated to form a film, the cross-linking agent contains an ether group, and a prefabricated film is obtained after drying at 60° C. to 100° C. for 24 h to 36 h;

[0099] (3) Ion treatment

[0100] Firstly, the prefabricated membrane is subjected to a first ion exchange treatment using a metal salt solution; and then the prefabricated membrane is subjected to a second ion exchange treatment using an alkali solution to prepare the anion exchange membrane.

[0101] The third aspect of the present application provides a use of the anion exchange membrane as described in the first aspect in the preparation of an electrolysis device.

[0102] A fourth aspect of the present application provides an electrolysis device, which comprises the anion exchange membrane as described in the first aspect and / or the anion exchange membrane prepared by the method for preparing the anion exchange membrane as described in the second aspect.

[0103] In some embodiments, the electrolysis device includes a cathode, an anode, an anion exchange membrane, and an electrolytic cell injected with an electrolyte. The cathode, anode, and anion exchange membrane are respectively disposed in the electrolytic cell, and the anion exchange membrane is disposed between the cathode and the anode.

[0104] The embodiments of the present application will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance provided in the present application, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0105] Example 1

[0106] (1) Polymer main chain

[0107] Under ice bath conditions, 4.6 g of p-terphenyl and 2.5 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane and mixed to obtain a first solution; a mixed solution containing 1.5 mL of trifluoroacetic acid and 16 mL of trifluoromethanesulfonic acid was added to the first solution, and after reacting for 6 hours, anhydrous methanol was added for precipitation, and the precipitate was washed to neutrality, and then vacuum dried at 60° C. for 24 hours to obtain a polymer main chain intermediate;

[0108] 1 g of the above polymer main chain intermediate was dissolved in 10 mL of NMP and 10 mL of DMSO, and then 0.5 g of potassium carbonate and 0.34 mL of methyl iodide were added, and quaternization reaction was carried out at 30° C. in the dark for 24 h, and then mixed with ethyl acetate for precipitation. The precipitate was washed with deionized water for several times, and then vacuum dried at 60° C. for 24 h to obtain a polymer main chain;

[0109] (2) Prefabricated membrane

[0110] 0.5 g of the polymer main chain obtained in step (1) was dissolved in 10 mL of DMSO, 0.04 mL of 1,2-di(2-chloroethoxy)ethane was added to the solution containing the polymer main chain and stirred for 24 h to obtain a casting solution, the casting solution was coated on a glass plate, and dried at 90° C. for 24 h to obtain a prefabricated membrane;

[0111] (3) Ion treatment

[0112] The prefabricated membrane is subjected to a first ion exchange treatment using a NaBr solution having a molar concentration of 0.5 mol / L; and then the prefabricated membrane is subjected to a second ion exchange treatment using a KOH solution having a molar concentration of 1 mol / L to prepare the anion exchange membrane.

[0113] Example 2

[0114] (1) Polymer main chain

[0115] Under ice bath conditions, 4.6 g of p-terphenyl and 2.5 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane to obtain a first solution; a mixed solution containing 1.8 mL of trifluoroacetic acid and 18 mL of trifluoromethanesulfonic acid was added to the first solution, and after reacting for 7 hours, anhydrous methanol was added for precipitation, and the precipitate was washed to neutrality, and then vacuum dried at 70° C. for 36 hours to obtain a polymer main chain intermediate;

[0116] 1 g of the above polymer main chain intermediate was dissolved in 10 mL of NMP and 10 mL of DMSO, and then 0.5 g of potassium carbonate and 0.3 mL of iodomethane were added, and quaternization reaction was carried out at 35° C. in the dark for 36 h, and then mixed with ethyl acetate for precipitation, and the precipitate was washed with deionized water for several times, and then vacuum dried at 60° C. for 24 h to obtain a polymer main chain;

[0117] (2) Prefabricated membrane

[0118] 0.5 g of the polymer main chain obtained in step (1) was dissolved in 10 mL of DMSO, 0.08 mL of 1,2-di(2-chloroethoxy)ethane was added to the solution containing the polymer main chain and stirred for 24 h to obtain a casting solution, the casting solution was coated on a glass plate, and dried at 120° C. for 24 h to obtain a prefabricated membrane;

[0119] (3) Ion treatment

[0120] The prefabricated membrane is subjected to a first ion exchange treatment using a NaBr solution having a molar concentration of 0.5 mol / L; and then the prefabricated membrane is subjected to a second ion exchange treatment using a KOH solution having a molar concentration of 1 mol / L to prepare the anion exchange membrane.

[0121] Example 3

[0122] (1) Polymer main chain

[0123] Under ice bath conditions, 4.6 g of p-terphenyl and 2.1 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane to obtain a first solution; a mixed solution containing 2 mL of trifluoroacetic acid and 20 mL of trifluoromethanesulfonic acid was added to the first solution, and after reacting for 8 hours, anhydrous methanol was added for precipitation, and the precipitate was washed to neutrality, and then vacuum dried at 100° C. for 36 hours to obtain a polymer main chain intermediate;

[0124] 1 g of the above polymer main chain intermediate was dissolved in 10 mL of NMP and 10 mL of DMSO, and then 0.6 g of potassium carbonate and 0.19 mL of iodomethane were added. The quaternization reaction was carried out at 40°C in the dark for 48 h, and then mixed with ethyl acetate for precipitation. The precipitate was washed with deionized water for several times and vacuum dried at 80°C for 30 h to obtain the polymer main chain. The FT-IR spectrum is shown as follows: Figure 1 As shown;

[0125] (2) Prefabricated membrane

[0126] 0.5 g of the polymer main chain obtained in step (1) was dissolved in 10 mL of DMSO, 0.2 mL of 1,2-di(2-chloroethoxy)ethane was added to the solution containing the polymer main chain and stirred for 24 h to obtain a casting solution, the casting solution was coated on a glass plate, and dried at 150° C. for 36 h to obtain a prefabricated membrane;

[0127] (3) Ion treatment

[0128] The prefabricated membrane is subjected to a first ion exchange treatment using a NaBr solution having a molar concentration of 0.5 mol / L; and then the prefabricated membrane is subjected to a second ion exchange treatment using a KOH solution having a molar concentration of 1 mol / L to prepare the anion exchange membrane.

[0129] Example 4

[0130] An anion exchange membrane was prepared according to the method of Example 3, except that the volume of the cross-linking agent 1,2-bis(2-chloroethoxy)ethane added was 0.02 mL.

[0131] Example 5

[0132] An anion exchange membrane was prepared according to the method of Example 3, except that the volume of the cross-linking agent 1,2-bis(2-chloroethoxy)ethane added was 0.3 mL.

[0133] Comparative Example 1

[0134] (1) Polymer main chain

[0135] Under ice bath conditions, 4.6 g of p-terphenyl and 2.3 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane and mixed to obtain a first solution; a mixed solution containing 1.6 mL of trifluoroacetic acid and 16 mL of trifluoromethanesulfonic acid was added to the first solution, and after reacting for 7.5 hours, anhydrous methanol was added for precipitation, and the precipitate was washed to neutrality, and then vacuum dried at 90° C. for 30 hours to obtain a polymer main chain intermediate;

[0136] 1 g of the above polymer main chain intermediate was dissolved in 10 mL of NMP and 10 mL of DMSO, and then 0.6 g of potassium carbonate and 0.6 mL of iodomethane were added. After quaternization reaction was carried out at 40°C in the dark for 48 h, it was mixed with ether for precipitation. The precipitate was washed with deionized water for several times and vacuum dried at 100°C for 36 h to obtain the polymer main chain. The FT-IR spectrum is shown as follows: Figure 1 As shown;

[0137] (2) Prefabricated membrane

[0138] Dissolve 0.5 g of the polymer main chain obtained in step (1) in 10 mL of DMSO, centrifuge to remove impurities to obtain a casting solution, apply the casting solution on a glass plate, and dry at 100° C. for 30 h to obtain a prefabricated membrane;

[0139] (3) Ion treatment

[0140] The prefabricated membrane is subjected to a first ion exchange treatment using a NaBr solution having a molar concentration of 0.5 mol / L; and then the prefabricated membrane is subjected to a second ion exchange treatment using a KOH solution having a molar concentration of 1 mol / L to prepare the anion exchange membrane.

[0141] Comparative Example 2

[0142] An anion exchange membrane was prepared according to the method of Example 3, except that in step (2), the cross-linking agent 1,2-di(2-chloroethoxy)ethane was replaced by 0.19 mL of dibromohexane.

[0143] The anion exchange membranes prepared in the above examples and comparative examples were tested for performance, and the testing method included:

[0144] Impedance test: The p-EIS method was used to detect the impedance of the anion exchange membrane at room temperature (25°C) using an electrochemical workstation (gamry);

[0145] Conductivity: The resistance at room temperature (25°C) was measured by the p-EIS impedance method, and the conductivity of the membrane was calculated by the formula σ=L / RA, (R is the impedance value of the membrane, L is the thickness of the membrane, and A is the effective area of ​​the membrane);

[0146] Tensile strength and elongation at break: A tensile machine (LABRD-V2.9) was used to test the tensile strength and elongation at break of the wet film. Figure 2 The figure is a comparison of the mechanical strength of the anion exchange membrane in Example 3 and Comparative Example 1;

[0147] Sol-gel fraction: a certain mass of dry film is placed in a DMSO solution at 80°C for 2 days, then the film is taken out and the surface solvent is washed off with deionized water, and then placed in a vacuum oven at 60°C to dry to constant weight, and the mass of the dry film is recorded. The sol-gel fraction is obtained by the formula GF = Wa / Wb×100% (Wb represents the mass of the dry film before the test, and Wa represents the mass of the dry film remaining after being dissolved in DMSO);

[0148] Alkali absorption rate: soak a membrane of a certain size in 1M KOH and soak it at room temperature for 24 hours, then take out the membrane and wipe the liquid on the surface with absorbent paper and weigh it, then wrap the membrane sample with absorbent paper and place it at 60℃ for vacuum drying for 24 hours, then weigh its dry weight, and use the formula W=(Wwet-Wdry) / Wdry ×100% (Wwet represents the mass of wet membrane, Wdry represents the mass of dry membrane) to detect the alkali absorption rate;

[0149] Microstructure characterization: The microstructure of the anion exchange membrane was determined using a transmission electron microscope (JEOL JEM-2000EX). Figure 4 The microscopic morphology comparison diagram of the anion exchange membrane in Example 3 and Comparative Example 1.

[0150] The test results are shown in Table 1.

[0151] Table 1

[0152]

[0153] The anion exchange membranes prepared in the above embodiments and comparative examples were assembled into an electrolysis device, in which the electrolyte was 1 mol / L KOH solution, the cathode was 2.3 mm compressed nickel foam, 0.6 mm raw carbon cloth and 0.3 mm catalyst carbon cloth, and the anode was 2.5 mm compressed catalyst nickel foam.

[0154] The current density of the electrolysis device was tested at 55°C and 2V. The polarization curves of the electrolyzed water of Example 3 and Comparative Example 1 were as follows: Figure 3 The test results are shown in Table 2.

[0155] Table 2

[0156]

[0157] From the above table we can see that:

[0158] (1) Compared with Examples 4-5, it can be seen that the present invention adjusts the mass ratio of the crosslinking agent to the polymer main chain, and has good microphase separation, higher ion conductivity and better electrolytic performance.

[0159] (2) Example 3 Compared with Comparative Examples 1-2, the present application uses an ether-containing cross-linking agent for cross-linking, which improves the mechanical properties of the anion exchange membrane, improves stability, and promotes microphase separation in the membrane, and its conductivity is significantly improved. The high ion conductivity improves its battery performance.

[0160] The present application first prepares the polymer main chain by Friedel-Crafts alkylation reaction; uses the Menxiujin reaction to realize the quaternization of the polymer main chain and then performs a cross-linking reaction; finally, the anion exchange membrane can be prepared by a casting method and alkalized to obtain a polymer membrane with different cross-linking degrees. The introduction of cross-linking groups containing ether groups not only improves the dimensional stability and mechanical properties of the membrane, but also improves the microphase separation structure in the membrane, and promotes the improvement of ion conductivity. The anion membrane prepared by the present application exhibits excellent alkali stability, high ion conductivity and excellent mechanical strength.

[0161] In summary, the present application adopts a cross-linking group containing an ether group to cross-link the polymer main chain, and the ether group in the cross-linking group can effectively induce the self-aggregation of the ionic group, thereby forming a developed ion transmission channel and effectively improving the conductivity. Moreover, the introduction of the cross-linking group into the anion exchange membrane can improve the anti-swelling performance, thereby improving the dimensional stability of the anion exchange membrane.

[0162] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0163] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the application. It should be noted that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An anion exchange membrane, characterized in that The anion exchange membrane comprises a plurality of polymer main chains and a plurality of cross-linking groups. The plurality of polymer main chains are cross-linked by the plurality of cross-linking groups, and the cross-linking groups contain ether groups.

2. The anion exchange membrane according to claim 1, characterized in that The cross-linking group includes a cross-linking main chain and a cross-linking side chain grafted onto the cross-linking main chain, and the cross-linking main chain and / or the cross-linking side chain contain an ether group.

3. The anion exchange membrane according to claim 1, characterized in that The anion exchange membrane satisfies at least one of the following conditions: (1) The polymer main chain comprises at least one of a polyaryl piperidine polymer, a polyaryl isatin polymer and a polybenzimidazole polymer; (2) The mass ratio of the polymer main chain to the cross-linking group is 1:(0.06~0.5).

4. A method for preparing an anion exchange membrane, characterized in that: The preparation method comprises: A solution containing a polymer main chain and a cross-linking agent are mixed to form a casting solution after cross-linking, and a prefabricated membrane is obtained after coating the casting solution, wherein the cross-linking agent contains an ether group; The prefabricated membrane is subjected to ion exchange treatment to prepare the anion exchange membrane.

5. The method for preparing an anion exchange membrane according to claim 4, characterized in that: The method for preparing the anion exchange membrane satisfies at least one of the following conditions: (1) The mass ratio of the cross-linking agent to the polymer main chain is (0.06-0.5):1; (2) The mass concentration of the polymer main chain in the solution containing the polymer main chain is 5% to 25%; (3) The crosslinking agent includes a polyhalogenated ether compound; optionally, the crosslinking agent includes at least one of 1,2-bis(2-chloroethoxy)ethane, 1,2-bis(2-bromoethoxy)ethane, 1,2-bis(2-iodoethoxy)ethane, 1,2-dichloro-1-ethoxyethane, 1,2-bis(4-chlorophenoxy)ethane, 1,2-bis(chloroacetoxy)ethane and 1,6-dibromo-2,5-dioxoperfluorohexane.

6. The method for preparing an anion exchange membrane according to claim 4, characterized in that: The ion exchange treatment comprises: Performing a first ion exchange treatment on the prefabricated membrane using a metal salt solution; Performing a second ion exchange treatment on the prefabricated membrane using an alkaline solution; Optionally, the metal salt contained in the metal salt solution includes at least one of NaBr, NaCl and KBr; Optionally, the alkaline compound contained in the alkaline solution includes at least one of potassium hydroxide, sodium hydroxide and calcium hydroxide.

7. The method for preparing an anion exchange membrane according to any one of claims 4 to 6, characterized in that: The preparation method of the polymer main chain comprises: mixing an aromatic monomer and a ketone monomer to obtain a first solution; Mixing the first solution and an acidic catalyst to prepare a polymer main chain intermediate; The polymer main chain intermediate, the acid binding agent and the halogenated alkane are mixed and quaternized to obtain the polymer main chain.

8. The method for preparing an anion exchange membrane according to claim 7, characterized in that: (1) The molar ratio of the aromatic monomer to the ketone monomer is 1 to 1.2:1; (2) The mass ratio of the halogenated alkane to the polymer main chain intermediate is (0.2-0.8): 1; (3) The mass ratio of the acid binding agent to the polymer main chain intermediate is (0.3-0.8): 1; (4) The aromatic monomer includes at least one of p-terphenyl, m-terphenyl, biphenyl, bibenzyl and 9,9'-diphenylfluorene; (5) The ketone monomer includes at least one of N-methyl-4-piperidone, isatin, 3-quininone, 1,1,1-trifluoroacetone and 2,2,2-trifluoroacetophenone; (6) The halogenated alkane includes at least one of methyl iodide, ethyl iodide and 2-iodopropane; (7) The acid binding agent includes at least one of potassium carbonate, sodium hydride, sodium bicarbonate, trimethylamine and sodium carbonate; (8) The acidic catalyst comprises at least one of trifluoroacetic acid, trifluoromethanesulfonic acid, methanesulfonic acid, perfluoropropionic acid, pentafluoroethanesulfonic acid and heptafluorobutyric acid; Optionally, the acidic catalyst includes trifluoroacetic acid and trifluoromethanesulfonic acid; further optionally, the molar ratio of the trifluoroacetic acid to the ketone monomer is 1-1.5:1; the molar ratio of the trifluoromethanesulfonic acid to the ketone monomer is 9-12:

1.

9. Use of the anion exchange membrane according to any one of claims 1 to 3 in preparing an electrolysis device.

10. An electrolysis device, characterized in that: The electrolysis device comprises the anion exchange membrane according to any one of claims 1 to 3 and / or an anion exchange membrane prepared by the method for preparing an anion exchange membrane according to any one of claims 4 to 8.

Citation Information

Patent Citations

  • Method for preparing cross-linked alkaline anion exchange membrane based on flexible long side chain polycation structure

    CN110690486A

  • Preparation method and application of cryptand cross-linked anion exchange membrane based on polyarylene piperidine copolymer

    CN115594807A

  • Perfluoro side chain grafted anion exchange membrane and preparation method thereof

    CN116845307A

  • Anion exchange membrane based on high free volume main chain and preparation method thereof

    CN117986651A

  • Cross-linked alkaline anion membrane based on cyclodextrin modification as well as preparation method and application of cross-linked alkaline anion membrane

    CN118185099A